Sosialisasi Dan Pendampingan Penggunaan Aplikasi Mendeley Bagi Mahasiswa Fakultas Bisnis Dan Humaniora Universitas Tjut Nyak Dhien Medan - Siregar, Dahris; Fadhilah, Cut Rafyqa (Universitas Pahlawan Tuanku Tambusai, 2024)
Insight is enhanced through this dedication, students' writing skills and their productivity in compiling scientific papers with the mendeley application. Mendeley is software that aids in the insertion, writing and completion of citations. This device is very useful for its users, especially students who make reference lists. Many people do not yet know the mendeley application and its benefits. Socialisation is the means by which this service activity is executed, training and mentoring. At the socialization stage, the concept of material about citation techniques using mendeley is disseminated quickly and effectively. Next, the second stage, training and mentoring, begins. Students are given instructions on how to install and utilise the mendeley programme directly in order to achieve the set goals. Students do not know or understand how to find and enter references and citations to the mendeley software, according to the findings of the discussion before the training. However, using the outcomes of the training subsequent to the distribution of the material, the practice and mentoring of students has proven to be very easy to apply the information they have learned by using the mendeley application directly.